Pemodelan Matematik Kinerja Pengering Surya Efek Rumah Kaca (ERK)-Hibrid Menggunakan Rak Berputar secara Vertikal - Sigit Triwahyudi; Bandul Suratmo; Budi Rahardjo; Leopold Oscar Nelwan (agriTECH, 2016)
This paper presents a performance test and mathematical modeling of greenhouse effect (GHE)-Hybrid solar dryer with vertical rotating rack. The dryer consists of a greenhouse dryer (1100 × 860 × 1300) mm with eight rack and additional heating system consists of a flat plate collector (1,04 m2), a hot water storage tank (197 liters) and a heat exchanger. To investigate the performance of solar greenhouse dryer, five experimental variation speed of rack were conducted (1, 4, 7, 10 rpm) and without rotation. Materials used in the experiment are local cardamom (Amomum cardamomum Wild). Weight of each experiment  about  9 to 10 kg. The average temperature of the hot water storage tank varies from 50.0 to 55.0 °C, drying air  temperature between 38.9 to 45.9 °C, while the relative humidity (RH) of drying chamber ranged from 32.1 to 47.4 %. Variation of rotational speed affects on the uniformity of product temperature and water content in each rack drying. At rotation 1 rpm  (experiment II), obtained  as the best conditions (temperature and moisture content are most uniform). Increasing rotational speed of rack causes increasing in standard deviation of  product temperature and moisture content. To simulate the performance of the dryer, mathematical modeling based on heat  and mass transfer and a thin layer drying  approaches were conducted. Equations solved numerically using the finite difference Euler with Visual Basic Application (VBA) program on Excel. Validation was conducted by comparing the calculation results of mathematical modeling (data prediction) with measurement data (data observation). Criterion validity was determined by  the value of the coefficient of determination (R2), the value of RMSD and MAPD. Mathematical models that have been developed can be described precisely the temperature of the hot water storage tank, temperature of the drying chamber, temperature of the product as well as a moisture content decrease. ABSTRAKMakalah ini menyajikan uji unjuk kerja dan pemodelan matematik pengering energi surya (ERK)-Hibrid  menggunakan  rak berputar secara vertikal. Pengering terdiri dari bangunan rumah kaca berukuran (1100 × 860 × 1300) mm dengan delapan buah rak dan sistim pemanas tambahan yang terdiri dari kolektor plat datar (1,04 m2), tangki penyimpan air panas (197 liter) dan penukar panas. Untuk mengetahuikinerja pengering energi surya, dilakukan lima kali percobaan variasi kecepatan putar rak (1, 4, 7, 10 ) rpm dan tanpa pemutaran rak. Bahan yang dipergunakan pada pengujian adalah kapulaga lokal (Amomum cardamomum Wild). Masing-masing percobaan seberat 9 sampai dengan 10 kg. Rata-rata suhu air tangki penyimpan panas bervariasi dari 50,0 sampai dengan 55,0 °C suhu ruang pengering antara 38,9 sampai dengan 45,9 °C, sedangkan kelembaban relatif (RH) ruang pengering berkisar antara 32,1 sampai dengan 47,4 %. Perlakuan pemutaran rak berpengaruh terhadap keseragaman suhu bahan maupun kadar air pada masing rak pengering. Pada perlakuan pemutaran 1 rpm (percobaan II), didapatkan kondisi terbaik (suhu bahan maupun kadar air yang paling seragam). Dengan kecepatan putar rak yang semakin meningkat menyebabkan nilai ragam suhu bahan maupun kadar air semakin meningkat. Untuk melakukan simulasi unjuk kerja dilakukan pemodelan matematik berdasarkan pindah panas dan massa serta pendekatan pengeringan lapisan tipis. Persamaan diselesaikan secara numerik menggunakan finite difference Euler dengan bantuan bahasa pemrograman Visual Basic Aplication (VBA) Excell. Validasi dilakukan dengan membandingkan antara perhitungan hasil pemodelan (data prediksi) dengan data hasil pengukuran (data observasi). Kriteria kevalidan ditentukan dengan melihat nilai koefisien determinasi (R2), nilai RMSD maupun nilai MAPD. Pemodelan  matematik yang telah dibangun dapat menggambarkan dengan tepat perubahan suhu air tangki penyimpan panas, suhu ruang pengering, suhu bahan maupun penurunan kadar air.